Desenvolvimento e trocas gasosas de plantas de cajueiro-anão precoce sob irrigação salina em neossolo quartzarênico - Araújo, Laíse Ferreira de (2013)
Most cashew orchards in Brazil are located in semiarid tropics, where water is scarce and has salinity problems. Thus, the physiology and development of clones of early dwarf cashew under saline conditions were assessed, both for plants grown in containers as in plants grown in the field. The experiments were conducted at the Experimental Station of Pacajus in Embrapa Agroindústria Tropical. The treatments consisted of, for twelve months, saline solutions adjusted to the electrical conductivity (ECw - 0.4, 1.5, 3.0, 4.5 and 6.0 dS m-1) in two clones of cashew (CCP 06 and BRS 265) in containers and a clone (CCP 06) in the field. In plants grown in containers, irrigation with saline water yielded an increase in the levels of Na and Cl in leaves, negatively affecting all variables of the two clones. The plants have the highest photosynthetic rates between 7:00 and 10:00 am, ideal period for measurements of gas exchange. There was no difference in tolerance between clones CCP 06 and BRS 265. Plants irrigated with ECw of 4.5 and 6.0 dS m-1 died before reaching the 12 month experiment. The root dry matter was more affected by salinity than the dry leaves. When grown in the field, irrigation with saline water in higher levels of salinity resulted in increased levels of Na and Cl in the leaves, but no significant difference in levels of salinity, for all variables of gas exchange and growth studied, except stomatal conductance and transpiration for the month of October (330 days after treatment application). Through the results of the daily course, it was seen that measurements of gas exchange must be made in the period between 8:00 and 10:00 am, for it is at this time that the plants have the highest photosynthetic rates, with lower values evapotranspiration of the plant. Clone CCP 06 was tolerant salinity conditions studied, in which most ECw applied was 6.0 dS m-1.